Obesity and Endometrial Cancer: Mechanism and How to Deal with? - Tricia Dewi Anggraeni; Raymond Surya; Andrew Pratama Kurniawan (PT Kalbe Farma Tbk., 2021)
Obesity is strongly associated with development of endometrial cancer more than any other cancer type. The relationship between obesity and endometrial cancer risk is combination of inflammation, insulin resistance, and increased bioavailability of estrogen. Obesity can increase risk to develop endometrial cancer as exogenous estrogen has impact for tumorigenesis. The best method to reduce the risk of endometrial cancer in obese women is through progesterone medication and lifestyle intervention. Obesitas erat kaitannya dengan terjadinya kanker endometrium lebih dari jenis kanker lainnya. Hubungan antara obesitas dan risiko kanker endometrium adalah kombinasi antara inflamasi, resistensi insulin, dan peningkatan bioavailabilitas estrogen. Obesitas dapat meningkatkan risiko terjadinya kanker endometrium karena estrogen eksogen berdampak pada tumorigenesis. Metode terbaik untuk mengurangi risiko kanker endometrium pada wanita yang obese adalah melalui pengobatan progesteron dan intervensi gaya hidup.